2011
DOI: 10.1002/lt.22431
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcome of infections in human immunodeficiency virus/hepatitis c virus-coinfected liver transplant recipients: A FIPSE/GESIDA Prospective Cohort Study

Abstract: Information about infections unrelated to acquired immunodeficiency syndrome (AIDS) in human immunodeficiency virus (HIV)-infected liver recipients is scarce. The aims of this study were to describe the prevalence, clinical characteristics, time of onset, and outcomes of bacterial, viral, and fungal infections in HIV/hepatitis C virus (HCV)-coinfected orthotopic liver transplant recipients and to identify risk factors for developing severe infections. We studied 84 consecutive HIV/HCV-coinfected patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 41 publications
4
46
0
1
Order By: Relevance
“…A multivariable analysis of the American cohort revealed a higher frequency of multisystem organ failure/sepsis in the coinfected group, likely the result of liver dysfunction related to severe HCV recurrence. The Spanish group reported that severe infections (defined as sepsis, bloodstream infections, invasive fungal infections, CMV disease, invasive viral infection, and mycobacterial disease) increased the mortality rate almost 3-fold [34]. In the American series, there were no graft losses related to HIVassociated infections or malignancies in the coinfected group.…”
Section: Treatment Of Hcv With Daas (P Stock N Terrault)mentioning
confidence: 98%
“…A multivariable analysis of the American cohort revealed a higher frequency of multisystem organ failure/sepsis in the coinfected group, likely the result of liver dysfunction related to severe HCV recurrence. The Spanish group reported that severe infections (defined as sepsis, bloodstream infections, invasive fungal infections, CMV disease, invasive viral infection, and mycobacterial disease) increased the mortality rate almost 3-fold [34]. In the American series, there were no graft losses related to HIVassociated infections or malignancies in the coinfected group.…”
Section: Treatment Of Hcv With Daas (P Stock N Terrault)mentioning
confidence: 98%
“…Preemptive therapy has not been well studied in some seropositive populations, including lung, heart, vascularized composite, pancreas, islet, and intestinal transplantation; prophylaxis may be preferable (weak, low). & Prophylaxis may be preferred in other high-risk patients, including those on recent antilymphocyte therapy, potent immunosuppression including desensitization or ABOincompatible protocols (including those on rituximab, bortezomib, eculizumab, and plasmapheresis/immunoadsorption), and those with HIV (weak, moderate) (145). & Transplant recipients on mammalian target of rapamycin (mTOR) inhibitors such as sirolimus and everolimus may have lower rates of CMV; (146Y152) whether this should alter their prevention strategy is unknown.…”
Section: Use Of Prophylaxis Versus Preemptive Therapymentioning
confidence: 99%
“…Most recently however, increased risk of infections was described in HIV infected liver transplant recipients with a history of AIDS, a high Model for End-Stage Liver Disease score or non-tacrolimus based immunosuppression 101. Accumulated experience in North America and Europe in the past 5 years indicated that 1 and 3 year survival rates in selected HIV infected recipients of liver transplants were almost similar to that of HIV negative recipients 102 103.…”
Section: How To Deal With End Stage Liver Disease In Coinfected Patiementioning
confidence: 99%